Fraud Triangle terhadap Financial Statement Fraud - Steven Steven; Carmel Meiden (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2020)
Abstract This study aims to analyze the effect of the fraud triangle on the financial statement fraud. Based on the theory of fraud triangle, there are three factors: pressure, opportunity, and rationalization. Sampling is done by purposive sampling method and obtained 19 sample companies with 57 observational data of manufacturing companies consumer goods industry sector listed on the Indonesia Stock Exchange in the period of 2017-2019. Hypothesis in this study is tested using descriptive statistics analysis, pooling test, and logistic regression analysis. The conclusion from this study proves that the variables of financial stability, financial targets and nature of industry have a positive effect on the financial statements fraud. While the variables of personal financial needs and ineffective monitoring have a negative effect on the financial statement fraud. However, the variables of external pressure and rationalization have no effect on the financial statement fraud. Abstrak Pengambilan sampel penelitian dilakukan dengan menggunakan metode purposive sampling dan diperoleh sebanyak 19 perusahaan sampel perusahaan dengan 57 data amatan pada sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia periode 2017-2019. Pengujian hipotesis dalam penelitian ini menggunakan analisis statistik deskriptif, uji pooling, dan analisis regresi logistik. Kesimpulan dari penelitian ini membuktikan bahwa variabel financial stability, financial targets, dan nature of industry berpengaruh positif terhadap financial statement fraud. Sedangkan personal financial need dan ineffective monitoring berpengaruh negatif terhadap financial statement fraud. Namun, external pressure dan rationalization tidak berpengaruh terhadap financial statement fraud.